Análises estruturais e evolutivas de uma região do gene COI do DNAmt de espécies de moscas saprófagas da família sarcophagidae e perspectivas para identificação taxonômica. - Rodrigues, Eduardo Leal (Universidade Federal de São Carlos, 2011)
The taxonomic classification system of all organisms has been traditionally based in the comparative analysis of a wide range of morphological structures. In the last decades, the potential of physiological, cellular and molecular characteristics have been recognized in taxonomy, including phylogenetic and biogeographic aspects. This study focuses on the structural and evolutionary characterization of a region encompassing the 3 end of the mtDNA gene COI from sarcophagids and analyzed the contribution of this information for species identification, increasing the knowledge related to this family in the neotropical region. The Sarcophagidae family has approximately 2,600 species and their phylogenetic relationships are not well established for most genera and sub-genera. In this scenario, the characterization of nucleotide sequences for species identification in Sarcophagidae is a strategic approach that contributes for inferring phylogenetic relationships in this family. In this study, a 470 bp region from the COI gene was sequenced and characterized by structural and evolutionary analyses for five species: Peckia anguilla, Peckia collusor, Peckia ingens, Oxysarcodexia admixta e Oxysarcodexia paulistanensis. For comparative analyses we included ortholog sequences from three other sarcophagid species (P. intermutans, O. ventricosa e S. carnaria) and from the species C. hominivorax (Calliphoridae) e Haematobia irritans (Muscidae) available in GenBank. The intraspecific variation showed values between 0 e 0,01 and the interspecific variation varied from 0,07 - 0,151. Similarly to other Diptera families, the nucleotide composition of this region showed a high content of A and T (on average: A = 30.2%; T = 38.7%; C = 17.3% and G = 13.8%). The aminoacid composition presents higher abundance of Leucine, Phenylalanine and Tyrosine. Only eight divergent aminoacid positions were identified in comparative analysis of sarcophagid species, in addition to 3 positions that diverges from the insect COI protein structural model. Neighbor-joining analysis using Kimura-2P, an usual procedure in DNA barcodes analysis, distributed all species in monophyletic clusters, however the utility of this approach for resolving taxonomical conflicts requires additional sampling of specimens/species including a wide geographical coverage in order to provide a better characterization of intraspecific variation in these species.
-
Keywords: genética molecular; DNA mitocondrial; Sarcophagidae - classificação; molecular identification; mtDNA; Sarcophagidae; COI; CIENCIAS BIOLOGICAS